Anatomical analysis of brain MRI in Alzheimer’s disease - Farzan, Ali; Mashohor, Syamsiah; Ramli, Abd Rahman; Mahmud, Rozi (International Institute of Engineers (IIE.org), 2014)
It is accepted that the onset of disease starts almost decades before appearing clinical symptoms. Developing new pharmacotherapeutic trials need to evaluate the effect of therapy in disease progression and it is ascertained that Neuroimaging based on high quality MR images is a useful way of dealing with this challenge. Various processing methods have been used to diagnose Alzheimer’s disease and evaluate strength of it in three major populations (AD, MCI and NC). Each of these methods has suggested that some anatomical structures or anatomically unspecified Regions of Interest (ROI) have been influenced by disease in various grades. This paper aims to survey the recent research in MRI Neuroimaging methods and evaluate the impact of various brain parts in AD diagnosing methods. A number of various regions in all of three main tissues (CSF, GM AND WM) suffer from the effects of disease. It is revealed that temporal lobe, hippocampus and cortex are the most important structures.